2008
DOI: 10.1245/s10434-007-9771-3
|View full text |Cite
|
Sign up to set email alerts
|

EGFR, HER2, and HER3 Expression in Laryngeal Primary Tumors and Corresponding Metastases

Abstract: The high frequency and stability in EGFR expression is encouraging for efforts to use EGFR targeting agents (e.g. Iressa, Tarceva, Erbitux or radiolabeled antibodies) for therapy of laryngeal carcinoma. For a few laryngeal carcinoma patients with HER2 overexpression, anti-HER2 agents could possibly be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 36 publications
4
52
0
3
Order By: Relevance
“…Sections, 4-µm thick, were cut and deparaffinized in xylene and hydrated through graded concentrations of ethanol to distilled water (14)(15)(16)(17). The samples were then stained with hematoxylin and eosin for routine clinical analysis and, for this specific research project, with immunohistochemical receptor staining, as described below.…”
Section: Patients and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections, 4-µm thick, were cut and deparaffinized in xylene and hydrated through graded concentrations of ethanol to distilled water (14)(15)(16)(17). The samples were then stained with hematoxylin and eosin for routine clinical analysis and, for this specific research project, with immunohistochemical receptor staining, as described below.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…EGFR was assessed by immunohistochemistry using a streptavidin-biotin complex technique as previously described (14,15,17). After deparaffinization of the sections, endogenous peroxidase was blocked in 0.3% H 2 O 2 in PBS for 20 min.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Wei et al reported EGFR overexpression in 87.5% of laryngeal primary tumors, of which 82.5% had lymph node metastases (17). CerbB2 overexpression occurred in only 10.5% of the cases while lymph node metastasis occurred in only 1% of the cases.…”
Section: Discussionmentioning
confidence: 98%
“…The radiolabeling of the molecules seemed to not disturb the binding to any significant degree, as indicated by the competitive administration of non-labeled substances to the cultured cells. Immunohistochemical stainings for HER2 were performed as described in several of our previous reports on clinical tumor samples (36,37). The digital image analyses of the autoradiographs were performed using modified versions of previously described procedures and software (12,38).…”
Section: Discussionmentioning
confidence: 99%
“…Staining was enzymatically developed with 3, 3-diaminobenzidine-tetra hydrochloride [DAB, Dako Sweden AB. Such procedures have been described in more detail (36,37)]. …”
Section: Growth Of Spheroidsmentioning
confidence: 99%